Medial calcification in the arterial wall of smooth muscle cell‐specific Smpd1 transgenic mice: A ceramide‐mediated vasculopathy. Issue 1 (19th November 2019) - Bhat, Owais M.; Yuan, Xinxu; Cain, Chad; Salloum, Fadi N.; Li, Pin‐Lan
Abstract: Arterial medial calcification (AMC) is associated with crystallization of hydroxyapatite in the extracellular matrix and arterial smooth muscle cells (SMCs) leading to reduced arterial compliance. The study was performed to test whether lysosomal acid sphingomyelinase (murine gene code: Smpd1 )‐derived ceramide contributes to the small extracellular vesicle (sEV) secretion from SMCs and consequently leads to AMC. In Smpd1 trg /SM cre mice with SMC‐specific overexpression of Smpd1 gene, a high dose of Vit D (500 000 IU/kg/d) resulted in increased aortic and coronary AMC, associated with augmented expression of RUNX2 and osteopontin in the coronary and aortic media compared with their littermates ( Smpd1 trg /SM wt and WT/WT mice), indicating phenotypic switch. However, amitriptyline, an acid sphingomyelinase (ASM) inhibitor, reduced calcification and reversed phenotypic switch. Smpd1 trg /SM cre mice showed increased CD63, AnX2 and ALP levels in the arterial wall, accompanied by reduced co‐localization of lysosome marker (Lamp‐1) with multivesicular body (MVB) marker (VPS16), a parameter for lysosome‐MVB interaction. All these changes related to lysosome fusion and sEV release were substantially attenuated by amitriptyline. Increased arterial stiffness and elastin disorganization were found in Smpd1 trg / SM cre mice as compared to their littermates. In cultured coronary arterial SMCs (CASMCs) from Smpd1 trg /SM cre mice, increased Pi concentrations led to markedly increased calcium deposition, phenotypic change and sEV secretion compared with WT CASMCs, accompanied by reduced lysosome‐MVB interaction. However, amitriptyline prevented these changes in Pi ‐treated CASMCs. These data indicate that lysosomal ceramide plays a critical role in phenotype change and sEV release in SMCs, which may contribute to the arterial stiffness during the development of AMC.